Adequate Employment, Underutilisation and Unemployment: An Analysis of Labour Force Outcomes for Australian Youth - Mitchell, W; Baum, S (My University, 2008)
This paper considers youth labour market disadvantage and presents an analysis which juxtaposes the role of individual supply characteristics with labour demand characteristics to advance an understanding of youth labour market outcomes. The paper takes the concept of employability and using data from the Household Income and Labour Dynamics Australia (HILDA) survey and the Australian Bureau of Statistics Household and Population Census develops probit regressions of separate labour force states against individual supply-side and regional level demand characteristics. The results illustrate the importance of considering both supply side and demand side characteristics when considering labour market outcomes and developing potential policy interventions.
Australian Journal of Labour Economics
Keywords: Employment; Employment -- Unemployment; Families; Employment -- Underemployment; Families -- Adolescents and Youth; Adolescents and youth; Families and relationships; Labour market; Employment; Families; Adolescents and Youth; Unemployment; Underemployment; Families and relationships; Adolescents and youth; Employment and unemployment